Orthodontic treatment in a patient with unilateral open-bite and Becker muscular dystrophy. A 5-year follow-up - Juan Fernando Aristizabal; Rosana Martínez Smit (Dental Press Editora, 2014)
INTRODUCTION: Becker muscular dystrophy is an X-chromosomal linked anomaly characterized by progressive muscle wear and weakness. This case report shows the orthodontic treatment of a Becker muscular dystrophy patient with unilateral open bite.METHODS: To correct patient's malocclusion, general anesthesia and orthognathic surgery were not considered as an option. Conventional orthodontic treatment with intermaxillary elastics and muscular functional therapy were employed instead.RESULTS: After 36 months, open bite was corrected. The case remains stable after a 5-year post-treatment retention period.